Aquatic invasions of the Nseleni River system: causes, consequences and control - Jones, Roy William (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Globalization has seen an unprecedented dispersal of exotic and alien species worldwide resulting in worldwide homogenization and sometimes extinction of indigenous or endemic taxa. When an exotic species becomes established in a new habitat the invasive organisms are capable of having an impact on indigenous community dynamics and the overall structure and function of ecosystems. Furthermore, the impact of invasion is determined by the geographical range, abundance and the per-capita or per-biomass effect of the invader. However, the success of the introduced organisms is reliant on their ability to acclimate to the physiochemical conditions of the newly invaded environment.Freshwater ecosystems are especially vulnerable to invasions because there are numerous potential routes of introduction including intentional pathways such as stocking, and unintentional pathways such as the release of ballast water and aquarium releases. Efforts to limit the introduction of invasive species or to manage established exotic populations are often hindered by insufficient understanding of the natural history of problematic species. Relatively little is known regarding the physiological tolerances of many taxa. Knowledge about specific species ecophysiological constraints allows for the prediction of future patterns of invasion more accurately, including where an introduced organism would probably survive, thrive and disperse. Furthermore, data on the physiological tolerances of an introduced exotic organism may provide data necessary for effective management and control. This studyinvestigated three invasive species in the Nseleni River system in a protected area in KwaZulu-Natal. The species studied were, Tarebia granifera (Quilted melania "“ Lamarck, 1822), Pterygoplichthys disjunctivus (Suckermouth armoured catfish - Weber, 1991) and Eichhornia crassipes (water hyacinth "“ (Martius) Solms-Laubach,). The Nseleni River flows into Lake Nsezi which is responsible for providing potable water to the surrounding towns and industry, as well as the surrounding rural communities. The Enseleni Nature reserve has become the centre for biodiversity dispersal in the immediate area, due to the change in landscape surrounding the protected area.An important step in developing alien invasive species management strategies in protected areas is determining their extent and invasive traits. Tarebia granifera is a prosobranch gastropod originally from South-East Asia that has become invasive in several countries around the world including South Africa. Snail populations were sampled at nine sites throughout the Nseleni/Mposa river system every six weeks over a twelve month period. The snail was abundant throughout the system, especially in shallow waters of less than 1m in depth.The first positive identification the loricariid catfish Pterygoplichthys disjunctivus for the Nseleni River was in 2006. The original introduction is believed to have been via the aquarium trade. The aim of the study was to assess the usefulness of the unified framework with regard to management of fish invasions by assessing the invasion stage of the loricariid population and identifying appropriate management actions using the Blackburn et al. (2011) framework. The fish were sampled at nine different sites and three different depths over a period of twelve months, as well as when two ichthyological surveys were carried out on the Nseleni River system. This invasive fish has been located throughout the system and both male and female fish were collected. The smallest fish sampled was a fingerling of a day or two old and the smallest pregnant female was a mere 270mm TL. This is a clear indication that this fish is breeding in the river system.Although T. granifera and P. disjunctivus were abundant in the Nseleni/Mposa river system, it was not clear what their role in the system was, and in particular if they were competing with any of the indigenous species. Therefore, isotope samples were collected from numerous taxa over a two week period, with the exception of Pterygoplichthys disjunctivus samples, which were collected over 12 months. The Î´13C and Î´15N signatures of all samples were determined. The niche overlap between the invasive and indigenous snails was effectively zero (1.02E-13%), indicating no shared food resources. The medium ranges of dNRb (7.14) and dCRb (9.07) for the invasive fish indicate that it utilizes a wider range of food resources and trophic levels than the majority of indigenous fish. A medium CDb value (2.34) for the invasive fish species, P. disjunctivus, describes medium trophic diversity, with three indigenous species possessing higher diversity and three possessing lower diversity. Furtherresults indicated that there was no direct dietary competition between P. disjunctivus and indigenous species. Eichhornia crassipes was first recorded on the Nseleni River in 1978, and has been shown to have a significant negative impact on the biodiversity of the Nseleni/Mposa River system and therefore required a control intervention. Although biological control using the two weevil species Neochetina eichhornia (Warner) and N. bruchi (Hustache) has been credited with affecting a good level of control, the lack of a manipulated post-release evaluation experiments has undermined this statement. Five experimental plots of water hyacinth of 20m2 were sprayed with an insecticide to control weevils. After ten months the plants in the sprayed plots were significantly bigger and heavier than those in the control plots that had natural populations of the biological control agents. This study has shown unequivocally that biological control has contributed significantly to the control of water hyacinth on the Nseleni/Mposa River system.The management plan for the Enseleni Nature Reserve identifies the need to control invasive and/or exotic organisms within the boundary of the protected area. In addition, set guidelines have been implemented on how to control these organisms, so that indigenous organisms are least affected. Lack of control of exotic organisms can have serious consequences for indigenous species. It is therefore of utmost importance that the population dynamics of the invading organism be understood, what the potential impact could be and how to control them. Furthermore, it has also acknowledged the threat of possible exotic species invasions from outside of the protected area that might result in threats to the protected area and that these must be investigated, researched and managed.This thesis has identified Tarebia granifera, Pterygoplichthys disjunctivus and Eichhornia crassipes as being a threat to indigenous biodiversity within the protected area, as well as in adjacent areas to the protected area. The thesis will therefore investigate the hypothesis that both Tarebia granifera and Pterygoplichthys disjunctivus are having a direct negative effect on available food resources for indigenous species of organisms. In addition, this thesis will investigate if theNeochetina species that have previously been introduced onto E. crassipes are having any negative effect on this invasive alien aquatic plant.
Keywords: Gastropoda -- South Africa; Introduced snails -- South Africa; Introduced mollusks -- South Africa; Loricariidae; Introduced fishes -- South Africa; Water hyacinth; Alien plants -- South Africa